Pengaruh Kemampuan Komunikasi Terhadap Kinerja Karyawan di Instansi Penerbangan: Studi pada Karyawan di UPBU Kelas 1 Mutiara Sis Al-Jufri Palu - Akbar Prasetyo Labaso; Adipura Danang Maulana (MES Bogor, 2024)
Effective communication is crucial for enhancing efficiency and human resource quality in aviation organizations like UPBU class 1 Mutiara Sis Al-Jufri Palu. Both leaders and employees rely heavily on communication to perform their tasks effectively. This research aims to assess the impact of communication skills on employee performance in this institution. The study employs a quantitative approach, collecting data through questionnaires and literature review. Comprehensive analysis includes testing data validity, reliability, and normality, as well as conducting simple linear regression analysis, partial t-tests, and coefficient of determination (R²) tests to evaluate the relationship between communication skills and employee performance at UPBU class 1 Mutiara Sis Al-Jufri Palu. The findings indicate that communication skills significantly influence employee performance, with an R Square value of 0.629, suggesting that approximately 62.9% of the variability in employee performance can be explained by their communication abilities